Concordância entre a avaliação clínica e videofluoroscópica em pacientes disfágicos - Costa, Cintia da Conceição (2014)
The current conception of speech therapy in dysphagia requires the use of a clinical assesment protocol that can provide sensitive and specific answers as to the degree of swallowing disorders. Objective: The objective of this research was to establish the correlation between the Dysphagia Risk Evaluation Protocol (DREP) and videofluoroscopy in patients with swallowing disorders as well as checking the level of oral intake after their assessment. Method: This research is exploratory, quantitative, longitudinal and retrospective in database. The sample consisted of 91 patients, 55 men and 36 women, aged between 18 and 89 years old. It was performed the clinical evaluation of dysphagia with the use of the Dysphagia Risk Evaluation Protocol - DREP (PADOVANI et al, 2007), use of the Functional Oral Intake Scale for Dysphagia in Stroke Patients - FOIS (CRARY et al, 2005), videofluoroscopic swallowing exam (VFSE) and use of the penetration/aspiration scale (ROSENBECK et al., 1996). The VFSE images were evaluated individually by three judges with expertise in dysphagia Results: The analysis of concordance of objective evaluation diagnosis between the judges according to the ICC was substantial and second Kappa index was considered moderate. The correlation between clinical (DREP) and objective assessment was moderate, it was found that the VFSE detected specific features of swallowing not identified in the clinical evaluation. The agreement between FOIS / DREP and FOIS / VFSE calculated by Kappa test was moderate, but the overall correlation was strong. Out of the 24 patients who received indication for total alternative feeding, that means, nothing orally, 13 (54%) received indication of at least one feeding consistency after completion of the VFSE. Furthermore, according to the clinical evaluation, 35 patients also needed an alternative feeding means and after the VFSE 25 patients still had indication for alternative feeding means. Conclusion: The DREP proved to be a satisfactory tool for establishing the presence of dysphagia in patients with different pathologies, but does not identify characteristics that are subject to analysis only with videofluoroscopy, confirming the necessary support of an objective method of assesment for a complete evaluation of the cases of dysphagia. There was strong correlation between the FOIS after clinical assessment by the DREP protocol and the videofluoroscopy of swallowing, the latter providing more accurate indication for the use of alternative feeding and liberation of oral feeding. Besides that, it was observed that the FOIS is an effective marker for determining the level of oral intake in dysphagia cases which were originated from neoplasms, diseases of the circulatory and respiratory systems.